The Role of TIMP-1 in the Regulation of Melanoma Growth and Immune Response Control : The Role of TIMP-1 in Melanoma Progression - Langguth, Miriam (My University, 2023)
TIMP-1 has recently emerged as a cytokine that mediates effects in immune cells. It is involved in proinflammatory conditions and is considered a poor prognosticator in many cancer types. However, its part in melanoma outcomes remains largely elusive. Moreover, the TIMP-1-mediated impact on immune and cancer cells has not been unveiled. The thesis assessed the role of TIMP-1 in regulating melanoma growth and immune response control. Briefly, TIMP-1 was evaluated for its prognostic potential and driver of immunogenic responses. Further, the specific impacts of TIMP-1 on the biological behavior of melanoma cells and immune cells were evaluated. We unveiled that high TIMP1 levels positively correlated with survival probability in cutaneous melanoma. In protein levels, activated immune cells expressed TIMP-1 more than tumor cell lines. TIMP-1 showed no direct effect on cancer cell proliferation and migration. In immune cells, TIMP-1 decreased phagocytosis in macrophages, increased DC differentiation, and the MHC-I and MHC-II cell surface expression. It restored CD8+ T cell proliferation in the presence of suppressive tumor factors. These results suggest that TIMP-1 is involved in the proinflammatory immune response that supports antigen presentation and CD8+ T cell survival. The results further indicate that the effects of TIMP-1 on cancer cells are based on the interaction with other cells in the TME. Further research into the effects of TIMP-1 on different subtypes of immune cells could elucidate its role in antitumor immune responses.
Keywords: TIMP-1, melanoma, immune cells